2009
DOI: 10.1634/theoncologist.2008-0268
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consenter Characteristics and Experience on Patient Interest in Clinical Research

Abstract: Learning Objectives Enumerate patient characteristics associated with participation in clinical trials. Compare the ways in which consenter characteristics may affect patient participation in clinical research. Evaluate the role of consenter experience in the process of enrolling patients in clinical research studies. This article is available for continuing medical education credit CCMMEE at http://CME.TheOncologist.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…They also found that patients approached by first-time consenters were significantly less likely to consent than those approached by seasoned consenters, underscoring the importance of good training of consenters. 7,22 There was no consensus among the participants about the best time to approach cancer patients for consent to donate their cancer tissue to science. Only one-third of them felt that consent should be asked prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that patients approached by first-time consenters were significantly less likely to consent than those approached by seasoned consenters, underscoring the importance of good training of consenters. 7,22 There was no consensus among the participants about the best time to approach cancer patients for consent to donate their cancer tissue to science. Only one-third of them felt that consent should be asked prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that participants with low overall motivation or motivation fueled by money/gifts tend to have more concerns and a poorer understanding of a long-term cohort study, potentially increasing the risk of dropout [17]. It was also reported that the experience of consenters affected the willingness of patients enrolled in a university-based cancer center tissue repository during follow-up and future research [18]. Communication between experienced ToMMo GMRCs and participants is therefore very important in maintaining or even increasing participant cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cancer patients are unaware that they might be eligible for a clinical trial, or that trials are conducted where they are receiving treatment [10]. Interest in a trial is predicated on respect for persons and may be associated with optimism [40], gender [41], more information (cancer site, age > 80 years, serious disease status) [13,32,33,38], type of intervention, marital status, race [42], physician communication styles [43], and other factors [27]. …”
Section: Methodsmentioning
confidence: 99%